KNOWLEDGE AND PREVENTION OF DEMENTIA AMONG THE ELDERLY - Kristanti Nupi; Santa Maria Pangaribuan; Sri Hunun Widiastuti (Nursing Current: Jurnal Keperawatan, 2022)
The elderly are in an unavoidable final stage of human development. The elderly will experience various changes, including decreased intellectual function. Apart from age, factors that cause intellectual changes in the elderly include dementia, which results in deficits in cognitive abilities, focuses on memory decline, and affects the decline in speech or language use. This study aimed to describe the knowledge of the elderly about dementia and their knowledge of dementia prevention efforts at the Cempaka Putih Public Health Center, Central Jakarta. This research method employed quantitative research with a descriptive design and sampling in this study used a convenience sampling technique with a total sample of 108 elderly respondents who visit the Cempaka Putih Health Center, Central Jakarta. The data collection method used two questionnaires, namely the dementia knowledge questionnaire and the dementia prevention knowledge questionnaire. A univariate analyze was performed in this study. The results showed that most of the elderly had poor knowledge about dementia, with a total of 72 respondents (66.7%) and 108 respondents (100%) had good dementia prevention. It is hoped that the results of this study can provide recommendations for developing effective programs to increase elderly health knowledge, especially about dementia and its prevention.